PENGEMBANGAN ALAT PENGENDALI HAMA WERENG COKLAT TANPA PESTISIDA BERTENAGA KINCIR ANGIN YANG RAMAH LINGKUNGAN - Rindra Yusianto; Usman Sudibyo; Wisnu Adi Prasetyanto (Teknoin, 2016)
Pests in rice crops, namely mice, stem borer and  Wereng Coklat (Nilaparvata lugens Stal). Wereng coklat  is classified as very dangerous for the rice crop. This pest is highly detrimental to the agricultural system in Indonesia, with attacks on a wide area in a short time. This pest control methods such as by controlling in farming, controlling the resistant varieties, physical controls and mechanical and biological control. That method is not effective, so a more practical way to control and quickly began to do that is chemically using pesticides. But the impact of pesticides is dangerous, especially due to the use unwisely. So that environmentally friendly technologies needed to control pests and ecosystem. Target of this research is to develop a prototype tool wereng coklat control without pesticides powered windmills that are environmentally friendly. Prototype are designed with two modes, namely automatic controlled with motion sensors and manual.  Prototype was designed with a mechanical concept that is environmentally friendly, it is to reduce the effects caused by the use of chemical pesticides. The purpose of this research is to design wereng coklat pest control device with a motion sensor that consists of a mechanical vacuum and aluminum propeller. The mechanical vacuum linked to the pipe that tipped on light suction funnel. In the suction funnel installed motion sensors that serve to detect the presence/movement wereng coklat pests.  The voltage source is derived from the modification of dry cell connected to a windmill which functioned as a generator. Dry cell store electricity converted from windmills. This study is experiment research with developed by tested prototype both pre and post test. The prototype developed by considering three factors: time of arrival (X1), time seedlings (X2) and the planting location (X3) against the number of catches (Y). This device does not use pesticides, but rather take advantage of the weakness of wereng coklat pest are very sensitive to light. Based on the test results we can conclude that the most influential variable to variable number of catches (Y) is variable Planted Area (X3) with a coefficient of 0.372. Then variable planting time (X2) with a coefficient of 0.355 and the smallest influence is variable arrival time (X1) with a coefficient of 0.140.